До проблеми формування культури мовлення в майбутнього вихователя - Мороз-Рекотова, Леся Вікторівна (БДПУ, 2015)
Стаття присвячена проблемі формування культури мовлення в майбутнього вихователя дошкільного навчального закладу, проаналізовано стан проблеми в психолого-педагогічній літературі, розкрито місце культури мовлення в професійній діяльності майбутнього вихователя дошкільного навчального закладу.
On the Problem of Forming a Culture of Speech in the Future Teacher
The article is devoted to the speech culture formation problem of the future teacher in the preschool educational institution. The state of this problem in psychological and pedagogical literature has been analyzed. The place of professional speech culture of the future teacher in the preschool educational institution has been discovered.
Keywords: культура мовлення; мовленнєва культура; комунікативно-мовленнєва культура; мовлення вихователя; speech culture; standard of speech; communicative speech culture; teacher's speech